A study on syntactic, semantic and pragmatic features of hyperbolic expressions in CEO news items in English versus Vietnamese - Chu Thị Mười (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
(i) to study hyperbolic expressions in English and Vietnamese CEO news items in terms of syntax, semantics and pragmatics; (ii) to find out the similarities and differences in syntactic, semantic and pragmatic features of HEs in English and Vietnamese CEO news items; (iii) to comprehend and translate HEs effectively in English and Vietnamese CEO news